2014
DOI: 10.1002/dc.23139
|View full text |Cite
|
Sign up to set email alerts
|

Cytological features of mammary analogue secretory carcinoma of salivary gland: Fine‐needle aspiration of seven cases

Abstract: Mammary analogue secretory carcinoma (MASC) is a recently described salivary gland neoplasm that is defined by ETV6‐NTRK3 gene fusion. There have been few case reports on the cytopathologic features of MASC to date. We examined the clinicopathological and cytological features of seven cases of MASC defined by RT‐PCR analysis of the ETV6‐NTRK3 fusion gene. The cases occurred in three men and four women aged between 39 and 68 years, with a mean of 51.6 years. In five of these seven cases, the tumor involved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 18 publications
1
44
1
Order By: Relevance
“…The reported cytological features of MASC are as follows [7,9,12,13,17,18] . (1) The nuclear shape is round to oval, with a smooth contour, and the nuclear atypia is mild to moderate with a fine or open chromatin pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The reported cytological features of MASC are as follows [7,9,12,13,17,18] . (1) The nuclear shape is round to oval, with a smooth contour, and the nuclear atypia is mild to moderate with a fine or open chromatin pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Staining for p63 and SMA was negative. This pattern of staining has been observed by most authors [1,3,4,5,6,7,8,9,10,11,12,13]. However, there have been reports of other salivary gland tumors expressing mammaglobin and S-100.…”
Section: Discussionmentioning
confidence: 69%
“…Mammaglobin staining was observed in 11% of the MEC and 6% of the PA cases studied by Bishop et al [4]. Higuchi et al [12] reported focal p63 expression in 2 of their 7 cases of MASC; however, localization of the stain, i.e. cytoplasmic or nuclear, was not clarified.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations